(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper presents the estimation of ripples by using analytical method in active power filters .This method is based on an average model of PWM voltage source inverter. The formulae for the ripple magnitude are derived for singlephase and three-phase three-leg structures. Numerical examples for filters generating third and fifth order harmonics are presented. The reactive component of fundamental harmonic is considered as an example. A ripple current reduction method is proposed that does not require additional switching devices. A current ripple having twice the frequency component of the power supply is generated in the dc part when a single-phase pulse width-modulated inverter is used for a grid connection. The current ripple causes shortening of the lifetime of electrolytic capacitors, batteries, and fuel cells. Without increasing the number of switching devices, the proposed circuit realizes a dc active filter function because center tap of the isolation transformer is connected to the energy buffer capacitor.In addition, the buffer capacitor voltage is controlled by the commonmode voltage of the inverter. The features of the proposed circuit, control strategy, and experimental results are described, including the result of ripple reduction, to approximately 20% that of the conventional circuit